PROFESSIONAL COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN CHARACTER BUILDING OF STUDENTS - priatin, kunpriatin (Faculty of Administrative Science, Universitas Brawijaya, 2025)
This research aim’s to analyze the professional competence of Islamic Religious Education (PAI) teachers in character building of students at SD Negeri 3 Ubung Denpasar, a public elementary school located in a religiously and culturally diverse community. The background of the study arises from growing concerns over the increasing prevalence of deviant behaviors among elementary school-aged children, such as truancy, disrespect, and aggression, indicating a weak internalization of moral and spiritual values. As central figures in character education, PAI teachers are expected not only to master religious content but also to possess personal integrity, pedagogical skills, and social sensitivity to effectively transform religious values into students’ daily lives.This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The informants included PAI teachers, the principal, students, and parents. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings show that PAI teachers at SD Negeri 3 Ubung demonstrate a solid mastery of subject matter and an awareness of the importance of character education. However, their implementation still faces several challenges, such as time constraints, lack of contextual teaching methods, and limited training on localized character education.